2017
DOI: 10.1186/s12887-017-0965-y
|View full text |Cite|
|
Sign up to set email alerts
|

Full title: peripheral venous catheter complications in children: predisposing factors in a multicenter prospective cohort study

Abstract: BackgroundPeripheral venous catheterization (PVC) is frequently used in children. This procedure is not free from potential complications. Our purpose was to identify the types and incidences of PVC complications in children and their predisposing factors in a developing country.MethodsWe conducted a prospective observational multicenter study in five pediatric and pediatric surgery departments over a period of 2 months. Two hundred fifteen PVC procedures were conducted in 98 children. The times of insertion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
83
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(113 citation statements)
references
References 40 publications
(64 reference statements)
6
83
2
3
Order By: Relevance
“…However,it is difficult to perform a vein puncture and maintain a venous route because of the tiny peripheral blood vessels of premature infants. Also, repeated punctures can increase the risks of intracranial haemorrhage and infection . Umbilical vein, as a natural venous access, is easy to maintain for long‐time catheterisation.…”
Section: Discussionmentioning
confidence: 99%
“…However,it is difficult to perform a vein puncture and maintain a venous route because of the tiny peripheral blood vessels of premature infants. Also, repeated punctures can increase the risks of intracranial haemorrhage and infection . Umbilical vein, as a natural venous access, is easy to maintain for long‐time catheterisation.…”
Section: Discussionmentioning
confidence: 99%
“…Harm associated with inappropriate PIVC insertion and management is an under-recognised patient safety issue. Local and national studies have demonstrated, after successful insertion, pediatric PIVCs are associated with high rates of local and systemic complications, including infiltration/extravasation, occlusion and dislodgment (Ben Abdelaziz et al, 2017;Malyon et al, 2014). Bloodstream infections associated with PIVCs are rare but can be fatal (Webster, Osborne, Rickard, & Marsh, 2019); and the volume of PIVCs used entails a significant associated burden on the healthcare system.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that more than 70% of hospitalized children are subjected to peripheral IV puncture (Negri, Avelar, Andreoni, & Pedreira, ) Over the years, many methods have been developed to assist in inserting and securing peripheral IV lines more effectively. These include visualization devices, venous distension devices, transillumination methods and ultrasound‐guided techniques which help in identifying an appropriate vein (Ben Abdelaziz et al, ; Mbamalu & Banerjee, ). Bedside methods like gently tapping on the vein, tourniquet application, asking patients to clench and relax their hands, and hanging the arm down are known to improve venous visibility (Kaur, Kaur, & Patel, ).…”
Section: Introductionmentioning
confidence: 99%